Thermoplastic Starch–Based Composite Reinforced by Conductive Filler Networks: Physical Properties and Electrical Conductivity Changes during Cyclic Deformation - Hamed Peidayesh (MDPI AG, 2021)
Conductive polymer composites (CPC) from renewable resources exhibit many interesting characteristics due to their biodegradability and conductivity changes under mechanical, thermal, chemical, or electrical stress. This study is focused on investigating the physical properties of electroconductive thermoplastic starch (TPS)–based composites and changes in electroconductive paths during cyclic deformation. TPS–based composites filled with various carbon black (CB) contents were prepared through melt processing. The electrical conductivity and physicochemical properties of TPS–CB composites, including mechanical properties and rheological behavior, were evaluated. With increasing CB content, the tensile strength and Young’s modulus were found to increase substantially. We found a percolation threshold for the CB loading of approximately 5.5 wt% based on the rheology and electrical conductivity. To observe the changing structure of the conductive CB paths during cyclic deformation, both the electrical conductivity and mechanical properties were recorded in parallel using online measurements. Moreover, the instant electrical conductivity measured online during mechanical deformation of the materials was taken as the parameter indirectly describing the structure of the conductive CB network. The electrical conductivity was found to increase during five runs of repeated cyclic mechanical deformations to constant deformation below strain at break, indicating good recovery of conductive paths and their new formation.